Under what conditions do rules-based and capability-based management modes dominate? - Lukas Michel; Johanna Anzengruber; Marco Wölfle; Nick Hixson (Risks, 2018)
Despite real changes in the work place and the negative consequences of prevailing hierarchical structures with rigid management systems, little attention has yet been paid to shifting management modes to accommodate the dynamics of the external environment, particularly when a firm's operating environment demands a high degree of flexibility. Building on the resource-based view as a basis for competitive advantage, we posit that differences in the stability of an organization's environment and the degree of managerial control explain variations in the management mode used in firms. Unlike other studies which mainly focus on either the dynamics of the external environment or management control, we have developed a theoretical model combining both streams of research, in a context frame to describe under what conditions firms engage in rules-based, change-based, engagement-based and capability-based management modes. To test our theoretical framework, we conducted a survey with 54 firms in various industries and nations on how their organizations cope with a dynamic environment and what management style they used in response. Our study reveals that the appropriate mode can be determined by analyzing purpose, motivation, knowledge and information, as well as the degree of complexity, volatility and uncertainty the firm is exposed to. With our framework, we attempt to advance the understanding of when organizations should adapt their management style to the changing business environment.
Keywords: 330; capabilities; management style; dynamics; change; engagement; VUCA; volatility; uncertainty; complexity